'What I Really Needed Was the Truth'. Exploring the Information Needs of People with Complex Regional Pain Syndrome. (15th June 2015) - Grieve, Sharon; Adams, Jo; McCabe, Candida
Abstract: Background: UK guidelines indicate that individuals with complex regional pain syndrome (CRPS) require information and education to support self‐management. The present qualitative study explored the specific information requirements of patients with CRPS and provides insight into how health professionals can best provide this. Methods: Following informed consent, eight semi‐structured telephone interviews were conducted with adults living with CRPS. Participants were asked about their experience of receiving information since diagnosis and the information that they would prefer to receive. Interviews were transcribed and data analysed using thematic analysis. Results: Two themes related to individuals' experience of receiving information. These were: 'Facing the unknown', which describes how participants reported that little information was available and the impact of this; and 'The need to be an expert', which describes how they needed to be proactive to seek this information themselves. Three themes related to the information that the individual would choose to receive. These were: 'Seeking the truth', which describes the need for knowledge – particularly accurate, honest information; 'The shared experience', which describes the positive and negative aspects of sharing information with others experiencing CRPS; and 'Access to expertise', which describes the need for access to reliable information, resources and expertise. Conclusion: The reported lack of information resulted in a struggle for participants to understand their condition, and access professional expertise and appropriate treatments. Health professionals require access to accurate information in order to share this with individuals with CRPS in a timely manner. Easily accessible and high‐quality patient resources to facilitate early referral for expertise are required. A central resource to identify local expertise would be valuable.